Pemberdayaan Umkm Ibu Pkk Menuju Perintisan Desa di Wilayah Desa Jembrak Kecamatan Pabelan Kabupaten Semarang - Dyah Palupiningtyas; Guntur Suryaning Hadi; Ray Octafian (Jurnal Pengabdian Masyarakat Waradin, 2022)
This activity aims to provide solutions for partners in dealing with Small and Medium Enterprise (UMKM) problems in tourist villages. Jembrak Village is a village in the Pabelan sub-district, Semarang, Central Java. The characteristics of this village are advanced and the beautiful environment is still there. Jembrak Village is about management and marketing. The management itself is how to manage Small and Medium Enterprises (UMKM) themselves in terms of the lack of community interest, ignorance of finance, management systems, and marketing. The remarketing is online marketing, where most of the owners of Small and Medium Enterprise (UMKM) find it difficult to use applications and online marketplaces, methods of proper promotion, and to administrative issues related to the use of social media to market their products. For this reason, the PKK Community Service team carried out activities including: 1) Observing Small and Medium Enterprise (UMKM) targets, 2) Conducting outreach about the Product Management and Marketing, 3) Provide a direct training on Product Management and Marketing, 4) Monitor and evaluate UMKM Pioneers in Jembrak Tourism Village. The implementation of this community service activity has gone well. Thanks to the cooperation between the committee and the support of various parties. However, there were a number of things that were noted after the activity took place, namely, the training participants needed ongoing assistance after this activity, because there were still many training participants who were unable to manage UMKM.